2020
DOI: 10.1111/ejh.13532
|View full text |Cite
|
Sign up to set email alerts
|

Image‐guided core needle biopsy as the first‐line diagnostic approach in lymphoproliferative disorders—A review of the current literature

Abstract: The World Health Organization (WHO) and numerous expert guidelines for lymphoma diagnosis and subclassification advocate the use of histology from surgical nodal excision biopsy (SEB) over core needle biopsy (CNB) due to perceived higher diagnostic yield. CNB is associated with lower morbidity and is more cost‐effective compared to SEB. Furthermore, current practice increasingly demonstrates material obtained from CNB can rapidly diagnose individuals with a clinical suspicion of lymphoma and allow initiation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 40 publications
1
14
0
3
Order By: Relevance
“…In recent decades, CNB has virtually become one of the initial diagnostic methods for lymphoma in many centers [10]. Additionally, the recently published literature review article confirmed the usefulness of CNB because of its diagnostic efficacy, reproducibility, and safety [11]. In this review, CNB demonstrated a high diagnostic rate (79–97%), high reproducibility among pathologists (87–93%), and minimal invasiveness.…”
Section: Introductionmentioning
confidence: 59%
“…In recent decades, CNB has virtually become one of the initial diagnostic methods for lymphoma in many centers [10]. Additionally, the recently published literature review article confirmed the usefulness of CNB because of its diagnostic efficacy, reproducibility, and safety [11]. In this review, CNB demonstrated a high diagnostic rate (79–97%), high reproducibility among pathologists (87–93%), and minimal invasiveness.…”
Section: Introductionmentioning
confidence: 59%
“…[8][9][10][11] Several attempts have been made in this patient setting to define the best first-line interventional diagnostic strategy to obtain pathological lymph node tissue. 12 There is the need to achieve accuracy of the diagnostic evaluation, while reducing adverse events, costs and waiting time for the performance of a biopsy, that is, the need for a true cost-effective interventional procedure. We reported in Annals of Hematology in 2017 13 encouraging single-centre efficacy and safety results of a prospective trial in which 376 patients with lymph node enlargement suspected of lymphoma were randomly assigned to biopsy with either standard surgery [open surgical biopsy (OSB)] or power Doppler ultrasonography (PDUS)-guided 16-G modified Menghini CNB.…”
Section: ;190:837-50mentioning
confidence: 99%
“…Several attempts have been made in this patient setting to define the best first‐line interventional diagnostic strategy to obtain pathological lymph node tissue 12 . There is the need to achieve accuracy of the diagnostic evaluation, while reducing adverse events, costs and waiting time for the performance of a biopsy, that is, the need for a true cost‐effective interventional procedure.…”
Section: Characteristic All Patients True‐positive Cnb False‐negativementioning
confidence: 99%
“…Accurate diagnosis with full histological subclassification relies on obtaining an adequate tissue sample. WHO and other expert-developed guidelines for lymphoma diagnosis recommend whole node surgical excision biopsy (SEB) as the preferred diagnostic investigation for suspected lymphoma 9–12. However, recent improvements to radiological and histopathological techniques may make core needle biopsy (CNB) more acceptable than previously thought.…”
Section: Introductionmentioning
confidence: 99%
“…However, recent improvements to radiological and histopathological techniques may make core needle biopsy (CNB) more acceptable than previously thought. One recent review reports a median diagnostic yield with full lymphoma subtyping of 92% for CNB cases, while 97.5% of SEBs were fully diagnostic 9. Another recent study found that 7% of patients required a second biopsy due to inadequate tissue after undergoing CNB 13.…”
Section: Introductionmentioning
confidence: 99%